The effects of three hamstring programmes on strength and sprinting performance in female footballers: A randomised controlled trial - Whyte, E.; O`Connor, S.; Connolly, A.; Hession, E.; Kennedy, J.; O`Boyle, B.; Thorp, J.; Timmons, S.; Burke, A. (PLOS ONE, 2026)
Objective Hamstring strain injuries (HSIs) frequently occur in female football, with sprinting being a common mechanism of injury. During sprinting, the considerable strength requirements of the knee flexors and hip extensors indicate their importance in performance and may partially explain the high incidence of HSIs. This study examined the effectiveness of 3 interventions on hip extensor and knee flexor strength and sprint performance in female footballers using a randomised controlled study design (ClinicalTrails.gov: NCT0573327).